Feasibility and Utility of Telephone-Based Psychological Support for People with Brain Tumor: A Single-Case Experimental Study - Jones, Stephanie; Ownsworth, Tamara; Shum, David H. K. (Frontiers in Oncology, 2015)
Rates of psychological distress are high following diagnosis and treatment of brain tumor. There can be multiple barriers to accessing psychological support, including physical and cognitive impairments and geographical limitations. Tele-based support could provide an effective and more flexible option for delivering psychological interventions. The present study aimed to investigate the feasibility and utility of a telephone-based psychotherapy intervention for people with brain tumor. A single-case multiple-baseline design was employed with a 4-7 week baseline phase, 10-week treatment phase and 5-week maintenance phase including a booster session. Four participants with a benign or malignant brain tumor (3 males & 1 female; aged 34 to 49 years), received 10 sessions of tele-based therapy and a booster session at four weeks post-treatment. Levels of depression, anxiety, and illness cognitions were monitored on a weekly basis throughout each phase whilst measures of quality of life, stress and self-concept were administered at the start and end of each phase. Weekly measures were analysed using a combination of both visual analysis and Tau-U statistics. Of the four participants, two of them demonstrated significant gains in mental health (depression and/or anxiety) and a significant decrease in their levels of helplessness (p<.05). The other two participants did not show gains in mental health or change in illness cognitions. All participants reported improvement in quality of life post-treatment. The results of the study provide preliminary support concerning the feasibility and utility of tele-based therapy for some people with brain tumor. Further research examining factors influencing the outcomes of tele-based psychological support is needed.